The significance of personalized medicine in healthcare services of the 21st century: a brief literature review - Uğraş Tiryaki, Ebru (The European Research Journal, 2024)
In modern healthcare services, patient safety is a primary goal. With technological advancements, the complexity of healthcare services increases, which in turn creates increased pressure on health professionals during decision-making processes and can lead to errors worldwide. Communication gaps, human factors, patient-originated issues, technical failures, and inadequate policies have been identified as the main causes of medical errors. While research shows that errors stem from human nature and are inevitable, it is emphasized that it is possible to develop methods that enhance patient safety. Utilizing digital technologies to improve the quality and efficiency of healthcare services is a crucial strategy. Innovations such as wearable technologies, mobile devices, digital media-delivered education and consulting services, telehealth applications, 3D printers, clinical decision support systems, and implantable biosensors encompass advancements in the digital health field. This research aims to analyze the complex and dynamic structure of healthcare services in the 21st century, especially considering the opportunities presented by the integration of artificial intelligence and genomic data, within the scope of the relevant literature.